Recovery of nitrogen from maize residue and inorganic fertilizer in a maize-groundnut rotation system in humid tropics of Malaysia - Mubarak, A. R.; A. B., Rosenani; Anuar, A. R.; D., Siti Zauyah (2003)
Incorporation of crop residues after harvest may improve nitrogen (N) retention of tropical soils. A maize-groundnut rotation experiment was established in an Ultisol to study the recovery by the crop-soil system of N from mineral fertilizer and from the first maize residue. Out of the recommended N fertilizer for maize (150 kg N ha-1), 60 kg N ha -1 was applied in the form of ammonium sulphate (9.82 atom percent 15N excess) to the first maize crop and traced (for four crops) in the subsequent cropping system, with or without incorporation of crop residues. Similarly, N in the labelled residues of the first crop (maize) was also traced in the soil-crop system with incorporation of unlabelled crop residues. Recovery of fertilizer 15N by the first crop ranged from 20 to 22%. In the subsequent four crops, this value averaged 2% (but ranged from 0.4 to 6%). The proportion of fertilizer N retained in the soil (0-50 cm) after harvest of the first crop was 35 to 44% whereas after harvest of the subsequent crops, this proportion was 30 (but ranged from 24 to 34%) in crop residue treated plots and 22% (but ranged from 18 to 27%) in plots where crop residues were removed. Maize residue-N recovery in the subsequent three crops averaged only 5% (but ranged from 1 to 11%), being highest in the crop after crop residue incorporation. The corresponding recovery in the soil (0-50 cm) averaged across crops was 46% (but ranged from 40 to 52%). In tropical regions with high rainfall, conserving and decreasing soil N losses from mineral fertilizers could be achieved (in the long term) by the combined application of crop residues with mineral fertilizer.